Meningkatkan Kemampuan Siswa dalam Menulis Teks Deskriptif melalui Strategi Writer Workshop di SMP Negeri 2 Lahewa T.A. 2021/2022 - Yasminar Amaerita Telaumbanua; Elwin P Zebua; Sefeniati Gea (Neolectura, 2022)
Writing is the process of using symbols like letter of the alphabet, punctuation and spaces to communicate thoughts and ideas in a readable form. To write clearly it is essential to understand the basic system of a language. In learning writing, most of students could not achieve the 70 MCC. There were problem faced by the students in studying writing especially in descriptive text at the seventh grade of SMP Negeri 2 Lahewa in 2021/2022 namely: the students were lack of vocabularies, the students were unable to describe the object and the students were unable to identify topic, main idea, content from descriptive text. Thus, to overcome these problems, the researchers conducted a research by using Writer Workshop Strategy at the seventh grade of SMP Negeri 2 Lahewa in 2021/2022. So, to achieve the purpose, the researchers used Classroom Action Research (CAR). This research has been conducted in two cycles, which each cycle consisted of two meetings, and each meeting consisted of four steps, they were planning, action, observation, and reflection. The result of the data in Cycle I showed there were 2 students (8%); 5 students (20%), 3 students (12%), 10 students (41%) and 4 students (16%). While in Cycle II there were 15 students (62%) got score among 86-100, 5 students (20%) got score among 71-85, and 4 students (16%) got score among 56-70. Based on the result, it is concluded that Writer Workshop Strategy improved the students’ writing ability in descriptive text at the seventh grade of SMP Negeri 2 Lahewa in 2021/2022.